Evangelism and the Paradox of Europe and Christianity - Poll, E. W. van der (Evangelical review of theology, 2018)
The article reports that theologians and practitioners reflect on European evangelism through socio-religious context which includes three aspects such as secularization, postmodernism, or post-Christendom. It states that these three aspects leads to a certain barrier for the communication of the Gospel. The fourth aspect could be the paradox of Europe and Christianity. It notes that all the aspects are contradictory when intertwined.